A construction-from-parts-type 3D modeller for digital fabrication. (2015) - Lin, Jiaqing; Nishino, Hiroaki
Rapid progresses of 3D depth sensing and 3D printing technologies make digital fabrication an affordable technology for general public on daily life. Both experienced and novice users, who want to design and create new 3D geometric models, can readily acquire 3D object data by capturing their surrounding environments with consumer depth sensors, and produce physical prototypes by using desktop 3D printers. Although 3D modelling is a key technology to bridge a gap between the 3D acquisition with the depth sensors and the 3D printing, there is technically a deep valley preventing the novices from readily practicing the digital fabrication. We designed and developed a system enabling novices to edit the acquired 3D models with a set of simple operations for producing original 3D models. The system supports them to perform all phases, acquiring, modelling, and printing 3D models, through an integrated graphical user interface (GUI). We describe basic principle, architecture, implementation method, and some experiments conducted for verifying the effectiveness of the proposed system.